Exploring the role of bridging nodes linking adverse childhood experiences and psychological risk factors in suicidal ideation among MSM - Huifang Xu; Lulu Xu; Zuxin Wang; Chen Xu; Fan Hu; Yong Cai; Ying Wang (Scientific Reports)
Abstract This study investigates the interplay between distal adverse childhood experiences (ACEs) and proximal psychological risk factors in predicting suicidal ideation among men who have sex with men (MSM) using network analysis. A total of 1138 MSM completed self-reported questionnaires on demographics, ACEs, depression, anxiety, interpersonal needs, and suicidal ideation. We employed Gaussian graphical models to perform a network analysis that mapped the relationships between ACEs and proximal psychological variables and identified bridge nodes. Additionally, suicidal ideation was incorporated to reevaluate the network and explore the association between the identified bridge nodes and suicidal ideation. The results show that approximately 88.3% of participants reported experiencing ACEs, with an average occurrence of 3.4 types of ACEs. Suicidal ideation was reported by 31.3% of participants. Key bridging nodes in the psychosocial network included perceived burdensomeness, thwarted belongingness, feeling tired/having little energy, and excessive worrying. Perceived burdensomeness exhibited the strongest correlation with suicidal ideation, followed by thwarted belongingness. Moreover, neglect is strongly associated with suicidal ideation. Our findings suggest that ACEs are associated with suicidal ideation and may be linked to specific proximal psychological factors that correlate with and potentially exacerbate suicidal ideation. These findings provide support to the Interpersonal Theory of Suicide, which suggests that perceived burdensomeness and thwarted belongingness are vital psychological factors in the onset of suicidal ideation. Addressing and intervening in these bridging nodes could help reduce the influence of ACEs on suicide ideation within the MSM community.